New Data on Rhinogobius chiengmaiensis and Rhinogobius mekongianus in Thailand by DNA Barcoding and Morphological Methods - Siriluck Tuncharoen; Paiboon Panase; Nontree Panprommin; Eakapol Wangkahart; Supranee Ruenkoed; Keatipong Mongkolwit; Dutrudi Panprommin (Animals)
A combination of morphological analysis and DNA barcoding (partial sequences of the cytochrome c oxidase I (COI) gene) was used to differentiate four gobiid fish species in the family Oxudercidae. Rhinogobius chiengmaiensis and Rhinogobius mekongianus were found in Thailand, while Eugnathogobius siamensis and Pseudogobiopsis oligactis were used for comparative purposes. Morphological identification relied on appearances, counts, and measurements. The 707-base pair COI sequences from eleven samples of four gobiid species were compared with reference sequences in public databases to confirm their scientific names. The average AT content was 51.8 ± 0.5% and the GC content was 48.2 ± 0.5%. Intraspecific genetic distances ranged from 0.00–0.28%, while interspecific genetic distances ranged from 0.86–16.63%. A neighbor-joining (NJ) phylogenetic tree depicted the relationships among the COI sequences of these species. Morphological analysis and COI sequences successfully distinguished the four gobiid species. Notably, the COI sequences of R. chiengmaiensis, R. mekongianus, and E. siamensis were previously unreported, hence, this study is the first report to add their sequences to public databases. These results can serve as valuable information for the management of aquatic resources, conservation, and aquaculture efforts.